Resistensi Pengelolaan Wisata Religi di Makam Dalem Santri Kutaliman Banyumas - Sulkhan Chakim; Abdul Basit; Muhammad Ash-Shidiqy; Akhmad Roja Badrus Zaman (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2021)
Tourism is generally understood as a relationship between managers, local governments, local communities, business people, and tourists in the form of service interactions. In the context of religious tourism that is developing in Indonesia, especially tourism, it tends to increase sharply but in reality there are still many grave sites of the guardians that have not been managed with tourism standards. This study aims to explore how the resistance of religious tourism management to the tomb of Dalem Santri Kutaliman, in Banyumas district. The research approach used is qualitative with an interpretive paradigm. Data collection techniques used in-depth interviews, participatory observations, documentation that supports this research. The findings of this study are the tomb of Dalem Santri as a tourist attraction in an effort to community-based management raises resistance, in the form of 1) Rejection of minority groups for community-based management. 2) The interests of socio-religious investors in the development of facilities. 3) The process of institutionalization of management is hampered. Optimalization of education, empowerment and community advocacy is needed to reduce resistance in the management of the Dalem Santri Tomb.